A porcine model for studying the cardiovascular consequences of high‐thoracic spinal cord injury. (11th February 2020) - West, Christopher R.; Poormasjedi‐Meibod, Malihe‐Sadat; Manouchehri, Neda; Williams, Alexandra M.; Erskine, Erin L.; Webster, Megan; Fisk, Shera; Morrison, Charlotte; Short, Katelyn; So, Kitty; Cheung, Amanda; Streijger, Femke; et al.
Abstract : Key points: We have developed a novel porcine model of high‐thoracic midline contusion spinal cord injury (SCI) at the T2 spinal level. We describe this model and the ensuing cardiovascular and neurohormonal responses, and demonstrate the model is efficacious for studying clinically relevant cardiovascular dysfunction post‐SCI. We demonstrate that the high‐thoracic SCI model, but not a low‐thoracic SCI model, induces persistent hypotension along with a gradual reduction in plasma noradrenaline and increases in plasma aldosterone and angiotensin II. We additionally conducted a proof‐of‐concept long‐term (12 weeks) survival study in animals with T2 contusion SCI demonstrating the potential utility of this model for not only acute experimentation but also long‐term drug studies prior to translation to the clinic. Abstract: Cardiovascular disease is a leading cause of morbidity and mortality in the spinal cord injury (SCI) population, especially in those with high‐thoracic or cervical SCI. With this in mind, we aimed to develop a large animal (porcine) model of high‐thoracic (T2 level) contusion SCI and compare the haemodynamic and neurohormonal responses of this injury against a low‐thoracic (T10 level) model. Ten Yorkshire pigs were randomly subjected to 20 cm weight drop contusion SCI at either the T2 or the T10 spinal level. Systolic blood pressure (SBP), mean arterial pressure (MAP) and heart rate (HR) were continuously monitored until 4 h post‐SCI. Plasma noradrenaline (NA), aldosterone and angiotensin II (ANGII) were measured pre‐SCI and at 30, 60, 120 and 240 min post‐SCI. Additionally, two Yucatan pigs were subjected to T2‐SCI and survived up to 12 weeks post‐injury to demonstrate the efficacy of this model for long‐term survival studies. Immediately after T2‐SCI, SBP, MAP and HR increased ( P < 0.0001). Between decompression (5 min post‐SCI) and 30 min post‐decompression in T2‐SCI, SBP and MAP were lower than pre‐SCI ( P < 0.038). At 3 and 4 h after T2‐SCI, SBP remained lower than pre‐SCI ( P = 0.048). After T10‐SCI, haemodynamic indices remained largely unaffected. Plasma NA was lower in T2‐ vs . T10‐SCI post‐SCI, whilst aldosterone and ANGII were higher. Both chronically injured pigs demonstrated a vast reduction in SBP at 12 weeks post‐SCI. Our model of T2‐SCI causes a rapid and sustained alteration in neurohormonal control and cardiovascular function, which does not occur in the T10 model. Key points: We have developed a novel porcine model of high‐thoracic midline contusion spinal cord injury (SCI) at the T2 spinal level. We describe this model and the ensuing cardiovascular and neurohormonal responses, and demonstrate the model is efficacious for studying clinically relevant cardiovascular dysfunction post‐SCI. We demonstrate that the high‐thoracic SCI model, but not a low‐thoracic SCI model, induces persistent hypotension along with a gradual reduction in plasma noradrenaline and increases in plasma aldosterone and angiotensin II. We additionally conducted a proof‐of‐concept long‐term (12 weeks) survival study in animals with T2 contusion SCI demonstrating the potential utility of this model for not only acute experimentation but also long‐term drug studies prior to translation to the clinic.